Regulation of the aflatoxin-like toxin dothistromin by AflJ. Issue 6 (June 2015) - Chettri, Pranav; Ehrlich, Kenneth C.; Bradshaw, Rosie E.
Abstract: Biosynthesis by Aspergillus parasiticus of aflatoxin, one of the most potent known naturally occurring carcinogens, requires the activity of two regulatory proteins, AflR and AflJ, which are encoded by divergently transcribed genes within the aflatoxin gene cluster. Although the Zn2 Cys6 transcription factor, AflR, has been well-studied, the role of AflJ as a transcription regulatory factor is not well understood. An AflJ-like gene ( DsAflJ ) is also present in the genome of the pine needle pathogen Dothistroma septosporum and is similarly divergently transcribed from an AflR orthologue ( DsAflR ). These genes are involved in biosynthesis of dothistromin, a toxic virulence factor related to aflatoxin. DsAflJ mutants produced low levels of dothistromin (<25-fold less than wild-type); this was in contrast to earlier work with A. parasiticus AflJ mutants in which aflatoxin production was more severely impaired. As expected, complementation of D. septosporum mutants with an intact copy of the DsAflJ gene regained production of wild-type levels of dothistromin, although levels were not further increased by over-expression in multi-copy strains. However, heterologous AflJ genes from Aspergillus spp. were unable to complement DsAflJ mutants, suggesting that the proteins function differently in these species. Highlights: A homologue of the aflatoxin regulator AflJ regulates dothistromin biosynthesis. DsAflJ mutants had reduced levels of dothistromin toxin and gene expression. Overexpression of AflJ results in elevated levels of aflatoxin, but not dothistromin. Species-specificity of AflJ was suggested by lack of cross-species complementation.